2018
DOI: 10.1007/s40653-018-0203-2
|View full text |Cite
|
Sign up to set email alerts
|

The Fairy Tale Model: Secure Facility Therapist Perceptions

Abstract: The current exploratory qualitative study sought to investigate novice therapist experience of implementing a phased trauma recovery approach, the Fairy Tale Model (FTM), in secure accommodation in Scotland. Participants were ten therapists trained and supervised in FTM over a 6 month period. Therapists delivered FTM to 37 youth. Individual interviews with therapists were based on the objectives of FTM, and explored the benefits, challenges and facilitating factors for both youth and therapists. Perceived bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Managers’ views both supported and contrasted with the results of a qualitative study of therapist perceptions of Progressive Counting, an individualised brief exposure approach, delivered in secure units in Scotland. Although this is a different trauma-specific programme, Barron and Mitchell (2017b) reported that therapists identified gains for themselves, young people and units as a whole. Therapists gained trauma-specific knowledge, skills and confidence and young people were described as more motivated, less emotionally dysregulated and more able to solve problem.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Managers’ views both supported and contrasted with the results of a qualitative study of therapist perceptions of Progressive Counting, an individualised brief exposure approach, delivered in secure units in Scotland. Although this is a different trauma-specific programme, Barron and Mitchell (2017b) reported that therapists identified gains for themselves, young people and units as a whole. Therapists gained trauma-specific knowledge, skills and confidence and young people were described as more motivated, less emotionally dysregulated and more able to solve problem.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to managers, therapists who delivered a brief exposure therapy in secure units reported both similar and distinct barriers. Therapists, as with managers, reported limited therapy time and short duration placements but also reported feeling de-skilled by complex adolescent difficulties (Barron and Mitchell, 2017b). Therapists, as with young people, included their own internal experience as one of the barriers, albeit with a different trauma therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For all the quest for evidence-based or scientific approaches to practice, it is hard to find consistent, replicable examples of their efficacy, certainly in child and youth care. There is no strong or consistent evidence of programmatic interventions being effective in promoting children's upbringing (Gharabaghi, 2012) even among its advocates (Whittaker et al, 2015;Hanson and Lang, 2016;Bath, 2017; Barron and Mitchell, 2019). Even in those rare instances where it might be argued to do so, the significance of such interventions is secondary or at the very least dependent upon the role of the helping relationship in this process (Smith, 2015).…”
Section: Problems With Technical Instrumentalismmentioning
confidence: 99%